Distal Fibular Reconstruction Using Iliac Grafting and Emslie-Vidal's Ligamentoplasty after Exeresis of Single Renal Carcinoma Metastasis. (28th February 2020) - Maury, E.; Granier, C.; Sleth, C.; Peraut, E.; Maury, P.
Abstract : Introduction . Restoring lateral ankle stability following distal resection of the fibula is a difficult procedure for which several surgical techniques have been proposed. Each of these techniques has potential drawbacks. This report presents a new option for fibular reconstruction. Case Study . We report the case of a 68-year-old male with evolving pain in the left ankle throughout the past 3 months. Three years prior to consultation, he underwent left nephrectomy for clear-cell adenocarcinoma. A swelling on the external side of the left ankle was noticed upon clinical examination, with no signs of inflammation. The ankle was stable with normal mobility. Radiographic examination revealed a 4 cm lytic lesion on the lateral malleolus with internal and external cortical damages as well as invasion of the soft tissues. Neither lower peroneotibial nor tibiotarsial joints were invaded. Needle biopsy confirmed the presence of metastatic renal clear-cell adenocarcinoma. Consequently, large exeresis of this single metastasis was indicated while preserving functional integrity of the ankle. Following block resection of the distal fibula including the lower tibioperoneal joint, a bicortical autograft was positioned to abut against the external side of the talus. Emslie-Vidal's ligamentoplasty procedure was performed with half of the short peroneal passed under the pedal flexor, then in the bone abutment, and finally through a calcaneal bone tunnel. Peroneus muscles were stabilized using a fragment sampled from the Achilles tendon. Pain decreased in 3 months, and the ankle was stable with normal functionality at a 5-year follow-up. Discussion . Reconstruction of the lateral ankle following fibular resection is possible by reconstructing the external facet of the malleolus using an autograft associated with Emslie-Vidal's ligamentoplasty procedure, hence stabilizing both tibiotalar and subtalar joints. This surgical procedure allowed the patient to return to his daily activities with neither instability nor evolution towards short-term tibiotalar arthrosis.